Methods and Models for Estimating the Maturity of the Innovation Structure - I. A. Brusakova (Управленческие науки, 2019)
The paper presents a systematic approach to the analysis of digital transformation management processes that is proposed to be estimated by means of data on the innovative complexity and maturity of processes and projects of a modern enterprise. The innovation complexity is formalized as a set of multidimensional data on enterprise management processes, including the external environment, architecture, communication infrastructure data, key indicators of management process efficiency and enterprise innovation activity. The production model of corporate knowledge about the enterprise’s readiness for digital transformation has been is presented. Also, there have been provided a review of methods and models for assessing the maturity of processes or projects of organizations. The author has proposed the way of a managerial content for decision-making processes on readiness for enterprise digitalization formed using BIG DATA cognitive technologies of multivariate data analysis that can let implement a systemic approach to managing a digital enterprise.